2018
DOI: 10.1002/jcb.28155
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key biomarkers in diabetic nephropathy via bioinformatic analysis

Abstract: Diabetic nephropathy (DN) is a major cause of end‐stage renal disease. Although intense efforts have been made to elucidate the pathogenesis, the molecular mechanisms of DN remain to be clarified. To identify the candidate genes in the progression of DN, microarray datasets GSE30122, GSE30528, and GSE47183 were downloaded from the Gene Expression Omnibus database. The differentially expressed genes (DEGs) were identified, and function enrichment analyses were performed. The protein‐protein interaction network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 65 publications
(110 reference statements)
0
20
0
Order By: Relevance
“…Researchers have used microarray data from DN models of different species to determine molecular mechanisms and genetic factors involved in DN [15,16]. Previous bioinformatics analyses using human DN gene chip data (GSE47183) from the GEO database found that the VSIG4, CD163, C1QA, C1QB, MS4A6A, COL6A3, COL1A2, CD44, FN1, NPHS1, WT1, PLCE1, TNNT2, TNNI1, and TNNC1 genes played important roles in DN progression through ECM-receptor interaction, PI3K-Akt signaling pathway, focal adhesion, proteoglycans in cancer, and complement and coagulation cascades [17]. Yang et al [18] identified hub genes associated with DN using GSE30528 chip data, including VEGFA, ITGA3, ITGB5, COL4A3, COL4A5, CBLB, and CCL19.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have used microarray data from DN models of different species to determine molecular mechanisms and genetic factors involved in DN [15,16]. Previous bioinformatics analyses using human DN gene chip data (GSE47183) from the GEO database found that the VSIG4, CD163, C1QA, C1QB, MS4A6A, COL6A3, COL1A2, CD44, FN1, NPHS1, WT1, PLCE1, TNNT2, TNNI1, and TNNC1 genes played important roles in DN progression through ECM-receptor interaction, PI3K-Akt signaling pathway, focal adhesion, proteoglycans in cancer, and complement and coagulation cascades [17]. Yang et al [18] identified hub genes associated with DN using GSE30528 chip data, including VEGFA, ITGA3, ITGB5, COL4A3, COL4A5, CBLB, and CCL19.…”
Section: Introductionmentioning
confidence: 99%
“…WGCNA was performed in an independent study of large number of samples of multiple kidney diseases, avoiding the heterogeneity among different studies caused by a comprehensive analysis of multiple GEO datasets. Different from the analysis of DEGs [14][15][16], the genome-wide transcriptional co-expression network analysis has provided an unbiased description of gene expression network in DN. A gene module speci c for DN was identi ed re ecting the unique pathogenesis of DN.…”
Section: Discussionmentioning
confidence: 99%
“…Search Tool for the Retrieval of Interacting Genes (STRING) (version10.5) database was used to construct PPI network. Figuring out the protein-protein functional interactions would help us to nd possible mechanisms underlying the development of diseases, as described in previous study (29). In the current study, STRING database was used to construct PPI network of DEGs, and the combined score was set as more than 0.9.…”
Section: Methodsmentioning
confidence: 99%